Expression Pattern of Scavenger Receptors and Amyloid-? Phagocytosis of Astrocytes and Microglia in Culture Are Modified by Acidosis: Implications for Alzheimer S Disease - Eugenin-Leon, J (IOS Press, 2016)
The pathological hallmarks of Alzheimer s disease (AD) are amyloid-β (Aβ) plaques, neurofibrillary tangles, and glia activation. The pathology also includes vascular amyloidosis and cerebrovascular disease. Vascular compromise can result in hypoperfusion, local tissue hypoxia, and acidosis. Activated microglia and astrocytes can phagocytose Aβ through membrane receptors that include scavenger receptors. Changes in glial cells induced by extracellular acidosis could play a role in the development of AD. Here, we assess whether extracellular acidosis changes glial cell properties relevant for Aβ clearance capacity. Incubation of glial cells on acidified culture medium (pH 6.9 or 6.5) for 24-48h resulted in decreased cell diameter, with thinner branches in astrocytes, slight reduction in cell body size in microglia, a transient decrease in astrocyte adhesion to substrates, and a persistent decrease in microglia adhesion compared with control media (pH 7.4). Astrocyte Aβ phagocytosis decreased at pH 6.9 and 6.5, whereas microglia phagocytosis only transiently decreased in acidified media. Scavenger receptors class B member I (SR-BI) increased and scavenger receptors-macrophage receptors with collagenous structures (SR-MARCO) decreased in astrocytes cultured at pH 6.5. In contrast, in microglia exposed to pH 6.5, expression of SR-BI and SR-MARCO increased and fatty acid translocase (CD-36) decreased. In conclusion, the acidic environment changed the adhesiveness and morphology of both microglia and astrocytes, but only astrocytes showed a persistent decrease in Aβ clearance activity. Expression of scavenger receptors was affected differentially in microglia and astrocytes by acidosis. These changes in scavenger receptor patterns can affect the activation of glia and their contribution to neurodegeneration. © 2016 - IOS Press and the authors. All rights reserved.